2014
DOI: 10.1371/journal.pone.0098973
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside, a Flavonoid Compound, Inhibits Proliferation and Stimulates Osteogenic Differentiation of Human Osteosarcoma Cells

Abstract: Osteosarcoma, one of the most common malignant bone tumours, is generally considered a differentiation disease caused by genetic and epigenetic disruptions in the terminal differentiation of osteoblasts. Novel therapies based on the non-cytotoxic induction of cell differentiation-responsive pathways could represent a significant advance in treating osteosarcoma; however, effective pharmaceuticals to induce differentiation are lacking. In the present study, we investigated the effect of hyperoside, a flavonoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 39 publications
(37 reference statements)
2
48
0
Order By: Relevance
“…We examined the role of TGF-β/Smad signaling in the progression of fibrosis. We found that expression levels of TGF-β1, p-Smad2, and p-Smad3 induced by pressure overload were attenuated in Hyp-treated mice, which is consistent with previous findings [25]. Our data showed that Hyp reduced TGF-β/Smad signaling in hypertrophied hearts and inhibited collagen synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…We examined the role of TGF-β/Smad signaling in the progression of fibrosis. We found that expression levels of TGF-β1, p-Smad2, and p-Smad3 induced by pressure overload were attenuated in Hyp-treated mice, which is consistent with previous findings [25]. Our data showed that Hyp reduced TGF-β/Smad signaling in hypertrophied hearts and inhibited collagen synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…Osteoblastic differentiation is essential for proper bone formation [30], and disruption in the differentiation of osteoblast from mesenchymal stem cells is considered to be the main cause of OS [31]. OPN is reported to be necessary for the differentiation of osteoblast through the avb3-integrin-mediated cell signaling [32,33]. Alteration in OPN level may disrupt the differentiation signaling pathway which failed to promote the differentiation of OS cells, enhanced OS tumor growth and exhibited possible differentiation defects in OS cells [31,34].…”
Section: Role Of Osteopontin In Osteosarcoma Pathogenesismentioning
confidence: 99%
“…Demethylation of the compound VII with HI gave a solid, which was found to be identical in all respect with compound VI. These observations suggested that the compound VII must be naringenin 4"-methyl ether (Zhang et al, 2014;Grayer, 1989). This was further supported by the appearance of peak at m/z, 286 (M+, 2) in EIMS, in agreement with the molecular formula C16 H14 O5 of the compoundVII.…”
Section: Characterization Of Compound VI (5 7 4' -Trihydroxy Flavanmentioning
confidence: 54%
“…(Jayprakasam, 1993). Based on these observations the flavanone was identified as 5, 7, 4"-trihydroxy flavanone (Buckingham, 1995) (naringenin) (Figure 6) and the identity confirmed by CO-PC with authentic sample (Zhang et al, 2014) yellow under UV/NH3. It had λmax (MeOH) 287, 325sh and Rf (Table 3) characteristic of a typical flavanone.…”
Section: Characterization Of Compound VI (5 7 4' -Trihydroxy Flavanmentioning
confidence: 93%